REPRESENTING OTHERS CARL THOMPSON DALAM NOVEL TRAVELER'S TALE: BELOK KANAN BARCELONA - Prastowo, Galang; Wijaya, Ikha Adhi (Diksi, 2020)
(Title: Representing Others Carl Thompson  in The Novel "Traveler's Tale: Belok Kanan Barcelona"). This research appllied representing other Carl Thomson approach in a novel entitled Traveler's Tale: Belok Kanan Barcelona. Representing other in the mentioned novel was conducted to expound on how the writer portrays west and east culture as the travel writing. The writer applied Carl Thompson's Theory to indentifying Travelers Tale novel; Belok Kanan Barcelona from the representing other's concept trough descriptive and qualitative approach. The research result has shown that they appraise the west culture than the east culture - tend to belittle the east culture.  The revealing of the two differnt culture features is represented in a form of idiology in travel writing. Ergo, from this research, we can conclude that the writing technique tends to exergerating the west (self),  the comparison result  tends to belittle the east culture (others). Keywords: travel writing, representing other, carl thompson.